The effect of service quality on customers' satisfaction of inter-district public bus companies in the Central Region of Sarawak, Malaysia - Laisak, Adler Hilary; Rosli, Anita; Sa’adi, Nurzalikha (Canadian Center of Science and Education, 2021)
Service quality is a vital factor that influences customer satisfaction. For profit organizations such as public bus companies, high customer satisfaction is a sign for business success and the ability to create long-term relationships with their customers. This research is to assess the effects of service quality attributes on customers’ satisfaction towards service quality provided by inter-district public bus companies in the Central Region of Sarawak. The research adapted SERVQUAL model proposed by Parasuraman, Zeithaml and Berry (1988). A total of 400 respondents were obtained among inter-district public bus users through a convenient sampling method. The mean score for customers’ satisfaction was 2.24, which means the level of customer satisfaction towards the service quality of inter-district buses in the Central Region was low. Meanwhile, the result from the multiple regression analysis showed that service quality dimensions of empathy, assurance, and responsibility had significant effects on customers’ satisfaction. The inter-district public bus companies in the Central Region of Sarawak should improve their service quality by building and obtaining customer trust to keep existing customers and at the same time to attract potential customers. Good customers’ experience towards service and the power of word mouth are marketing tools to enhance business reputation relative to other competitors.